BREAST CANCER PROFILE IN VERY YOUNG WOMEN AT HAJI ADAM MALIK GENERAL HOSPITAL MEDAN (Sumatera Medical Journal, 2020)
Abstract. Breast cancer is the most kind of cancer that happens to women, and it’s one of the cancer that can cause the major death in the world and in Indonesia. Breast cancer cases at age are very young tend to have lower percentages of old age, but have a bad prognosis. Family history of breast cancer because of the BRCA1 and BRCA2 mutation . Objective. The aim of this research is to study about breast cancer very young age profile in H. Adam Malik Medan General Hospital. From 2016-2018 based on age, family history and grading histology. Methods. In this descriptive research with cross-sectional study, the sample were collected from medical record of breast cancer patient in H. Adam Malik Medan General Hospital. This research use total sampling method and matched with inclusion and exclusion criteria. Results. Total of the sample is 160 subject. The majority of age group is 31-35 year’s old (81 subject or 51,0%). The majority of age menarche group is